SURGICAL TREATMENT OF COSMETIC BODY DEFECTS IN MESOMORPHIC PATIENTS - Drabovskiy, V.S.; Avetikov, D.S.; Kapustianskyi, D.V.; Malyk, S.V.; Bezruchko, M.V.; Osipov, O.S. (World of Medicine and Biology, 2020)
A method for improving the stage of abdominoplasty in the trunk cosmetic defects correction in patients with mesomorphic body type, which provides retension suture with traction of the lateral edges of the upper transverse skin and fat flap with the rotation angle of 51– 58о in men and 54 – 61o in women in order to create a uniform tissue tension due to the biomechanical properties of the anterior abdominal wall tissues. This method, compared to the known ones, revealed the following advantages: formation of a normotrophic scar at the incision site, reduction of local wound complications and other adverse consequences of correction, obtaining a satisfactory cosmetic result of abdominoplasty and improving the quality of life in patients.
Keywords: abdominoplasty; cosmetic scar; mesomorphs